Eigen value approach for dual phase lag micropolar porous thermoelastic circular plate with ramp type heating. Issue 4 (13th November 2017) - Kumar, Rajneesh; Kaushal, Priyanka; Sharma, Rajni
Abstract : Purpose: The purpose of this paper is to investigate a two dimensional problem of micropolar porous thermoelastic circular plate subjected to ramp type heating. Design/methodology/approach: Three phase lag theory of thermoelasticity has been used to formulate the problem. A numerical inversion technique is applied to obtain the result in the physical domain. The numerical values of the resulting quantities are presented graphically to show the effect of porosity and dual phase lag model. Some particular cases are also presented. Findings: The Laplace and Hankel transforms are employed followed by the eigen value approach to obtain the components of displacements, microrotation, volume fraction field, temperature distribution and stresses in the transformed domain. Originality/value: This paper fulfils the need to study the two-dimensional problem of micropolar porous thermoelastic circular plate subjected to ramp type heating.